Pyruvate dehydrogenase and mitochondrial function in Huntington’s disease – influence of insulin/IGF and histone deacetylase inhibitors - Rodrigues, Joana Cristina P. (2012)
Dissertação de mestrado em Biologia Celular e Molecular apresentada ao Departamento Ciências da Vida da Faculdade de Ciências e Tecnologia da Universidade de Coimbra.